'Plain lignocaine' vs 'Lignocaine with vasoconstrictor'—Comparative evaluation of pain during administration and post-extraction wound healing by a double blinded randomized controlled clinical trial. (3rd July 2016) - Panneerselvam, Elavenil; Balasubramanian, Sasikala; Raja V. B., Krishnakumar; Kannan, Ravi; Rajaram, Krishnaraj; Rajendra Sharma, Aditi
Abstract: Objectives: The aim of this double blinded randomized controlled clinical trial was to evaluate the efficacy of two local anaesthetic solutions, 'Plain lignocaine' and 'Lignocaine with vasoconstrictor', on pain during administration and post-extraction wound healing in patients undergoing therapeutic extractions. Materials and methods: Fifty patients indicated for therapeutic extraction of upper and lower premolars for orthodontic purpose were recruited for the study. Using a split-mouth study design, anaesthesia was achieved using lignocaine with adrenaline on the control side and plain lignocaine on the study side. Pain perception was measured by modified visual analogue scale and wound healing was assessed by Landry's Wound Healing Index. Sample allocation was done by simple randomization. The outcome parameters compared were (1) pain during administration of LA and (2) post-operative healing after extraction. Data analysis involved Chi-square test to compare proportions between treatment groups and independent sample t -test to compare mean values between treatment groups. SPSS version 22.0 was used to analyse the data. Results: The study group demonstrated a statistically significant wound healing on day1 and day 3 between the study and control group with p < 0.001. In the control group 68% had severe pain, whereas only 2% had severe pain in the study group. The proportions between the two groups were statistically significant ( p < 0.001). Conclusion: The patients who received Plain Lignocaine perceived less pain during injection of local anaesthetic solution when compared to patients who received lignocaine with vasoconstrictor. The early post-operative wound healing was better in patients anaesthetized by Plain Lignocaine.